2016
DOI: 10.1074/mcp.m115.051078
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Secretome Analysis of Ralstonia solanacearum Type 3 Secretion-Associated Mutants Reveals a Fine Control of Effector Delivery, Essential for Bacterial Pathogenicity

Abstract: Ralstonia solanacearum, the causal agent of bacterial wilt, exerts its pathogenicity through more than a hundred secreted proteins, many of them depending directly on the functionality of a type 3 secretion system. To date, only few type 3 effectors have been identified as required for bacterial pathogenicity, notably because of redundancy among the large R. solanacearum effector repertoire. In order to identify groups of effectors collectively promoting disease on susceptible hosts, we investigated the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 62 publications
2
48
0
Order By: Relevance
“…Moreover, this reconstruction associates a metabolic network with a macromolecule network to account for the production and secretion of virulence factors since R . solanacearum is known to produce hundreds of extracellular proteins involved in pathogenesis [ 40 41 ]. R .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this reconstruction associates a metabolic network with a macromolecule network to account for the production and secretion of virulence factors since R . solanacearum is known to produce hundreds of extracellular proteins involved in pathogenesis [ 40 41 ]. R .…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial plant pathogens also employ hrp‐associated ( hpa ) proteins, such as chaperones and export control proteins, for coordinated delivery of T3Es into host cells (Lohou et al ., ). Recently, a proteomics approach to the R. solanacearum secretome identified differential T3E secretion patterns in hpaB , hpaD and hpaG mutant strains, which affected bacterial virulence and supports the idea of the hierarchical delivery of T3Es (Lonjon et al ., ). Mechanistically, it has been suggested that the global T3E export chaperone HpaB interacts with HpaA to select and guide T3Es to the T3SS‐associated ATPase HrcN for translocation (Büttner et al ., ; Chang et al ., ).…”
Section: Regulation Dynamics and Hierarchy Of Effector Translocationmentioning
confidence: 97%
“…Secreted proteins play important roles in a number of pathological processes, such as signal transduction [ 40 ] and defense [ 41 ]. Suspension-culture is a model system for studying the secreted proteins [ 42 ] and has been widely used for secretome analysis of interactions between plants and their pathogens including bacteria [ 43 ] and fungi [ 44 ]. In this study, we used this method to investigate the altered protein expression in resistant rice cells in response to Xoo inoculation.…”
Section: Discussionmentioning
confidence: 99%